Host species of freshwater snails within the same freshwater ecosystem shapes the intestinal microbiome - Hu, Zongfu; Tong, Qing; Chang, Jie; Xu, Junzhao; Wu, Baiyila; Han, Yongmei; Yu, Jianhua; Niu, Huaxin (Frontiers in Ecology and Evolution, 2024)
Freshwater snails are not only intermediate hosts for parasites but also an important part of the food chain as they convert plant biomass and humus into animal biomass. However, being widely distributed in freshwater environments, snails are highly affected by human activities, which makes their adaptation to altering environments challenging. The gut microbiome helps animals in their digestion, immune system, growth and adapting to changing environments. The effect of host species on intestinal microbial community has been poorly studied in snails.In this study, single-molecule real-time sequencing technology (SMRT) was used to obtain full-length 16S rRNA genes to determine the intestinal microbiomes of three species of freshwater snails (SQ: Sinotaia quadrata, BU:Boreoelona ussuriensis, RP: Radix plicatula) with similar feeding habits in a same water environment.Unifrac PCoAshowed distinct and significant segregation of the intestinal microbiomes of the three hosts (P<0.05) . The phyla Cyanobacteria, Proteobacteria, Firmicutes and Planctomycetota dominated snail guts. Only 25.26% of OTUs were identified up to species level, while 72.07% of OTUs were identified at the genus level. Although 72.94% of the total bacterial species (566) were common to three snails, significant differences were observed in terms of their abundance (P < 0.05). Several genera can help to determine the phenotype of the intestinal microbiota. In this case, Lelliottia contributed mainly to stress tolerance, biofilm formation, potential pathogenicity, mobile elements and facultatively anaerobic phenotypes in RP. Romboutsia and Clostridium_sensu_stricto_1 contributed to the anaerobic phenotype of SQ and RP, Pirellula contributed to the aerobic phenotype in SQ. Moreover, PICRUSt (Phylogenetic Investigation of Communities by Reconstruction of Unobserved States) predicted 68 GH (glycoside hydrolase) genes, with these including monosaccharide-, disaccharide-, polysaccharide-, and starch-digesting enzyme genes as well as enzymes specific to aquatic plants. Many of the identified pathways were related to Infectious diseases and Xenobiotics biodegradation and metabolism, which expanded the resistance of freshwater snails. Lelliottia, Romboutsia, Clostridium_sensu_stricto_1, and Pirellula play an important role in the intestinal microbiota phenotype of the host snails. In general, the host species affects the structure of the gut microbial community, which in turn helps gastropods improve their environmental adaptability, but further study is still needed.